Trial watch: Dendritic cell (DC)-based immunotherapy for cancer. (31st December 2022) - Laureano, Raquel S; Sprooten, Jenny; Vanmeerbeerk, Isaure; Borras, Daniel M; Govaerts, Jannes; Naulaerts, Stefan; Berneman, Zwi N; Beuselinck, Benoit; Bol, Kalijn F; Borst, Jannie; Coosemans, an; Datsi, Angeliki; et al.
ABSTRACT: Dendritic cell (DC)-based vaccination for cancer treatment has seen considerable development over recent decades. However, this field is currently in a state of flux toward niche-applications, owing to recent paradigm-shifts in immuno-oncology mobilized by T cell-targeting immunotherapies. DC vaccines are typically generated using autologous (patient-derived) DCs exposed to tumor-associated or -specific antigens (TAAs or TSAs), in the presence of immunostimulatory molecules to induce DC maturation, followed by reinfusion into patients. Accordingly, DC vaccines can induce TAA/TSA-specific CD8 + /CD4 + T cell responses. Yet, DC vaccination still shows suboptimal anti-tumor efficacy in the clinic. Extensive efforts are ongoing to improve the immunogenicity and efficacy of DC vaccines, often by employing combinatorial chemo-immunotherapy regimens. In this Trial Watch, we summarize the recent preclinical and clinical developments in this field and discuss the ongoing trends and future perspectives of DC-based immunotherapy for oncological indications.